SAT0348 CLINICAL SPECTRUM TIME COURSE OF ANTISYNTHETASE SYNDROME PATIENTS POSITIVE FOR ANTICENTROMERE ANTIBODIES. (2nd June 2020) - Zanframundo, G.; Sambataro, G.; Codullo, V.; Biglia, A.; Bozzalla Cassione, E.; Bravi, E.; Iannone, F.; Fornaro, M.; Triantafyllias, K.; Pesci, A.; Tomietto, P.; Molberg, Ø.; et al.
Abstract : Background: ASSD is characterized by antisynthetase antibodies (ARS) and the triad arthritis/myositis/Interstitial Lung Disease (ILD). ASSD and systemic sclerosis (SSc) may share features, like Raynaud's phenomenon (RP), capillaroscopic alterations, and also some SSc specific autoantibodies. Objectives: To evaluate the characteristics of ASSD + for anticentromere antibodies (ACA). Methods: Retrospective analysis of clinical and laboratory characteristics of ACA + ASSD. Patients were identified in an established international cohort, randomly matched 1:1 for sex, age, disease duration and ARS positivity with a group of ACA - ASSD. Results: 18 ACA + ASSD (15 females, 83%, 15 anti-Jo1, 2 anti-PL7, 1 anti-PL12 ARS) patients were identified. In comparison to ACA - group, no differences were observed in disease clinical presentation and evolution. Though, 9 ACA + patients (50%) satisfied the ACR/EULAR 2013 classification criteria for SSc and only 1 in ACA - group (p=0.007) (Table 1). An incomplete ASSD (lack of at least one triad finding) was observed in 15 patients in both ACA + and – group (p=1). Among these patients, 13 ACA + and 11 ACA – developed de-novo triad finding during disease course (p=0.651). In ACA + group, a de-novo arthritis was observed in 4 patients (vs 1, p=0.565), a de-novo myositis in 8 (vs 5, p=1), and a de-novo ILD in 7 (vs 10, p=1). The prevalence of complete forms was similar between ACA + and – group at both disease onset (3 vs 3, 17%, p=1) and last follow-up, (10 vs 11, 56% vs 61%, p=1). Of note, only 1 patient (6%) for each group died (p=1). Conclusion: The clinical spectrum time course of ACA+ and - ASSD is similar, even when ACA + patients could be classified as SSc. By considering the high prevalence of arthritis and myositis we observed, we suggest that ACA+ patients with arthritis and myositis, should be tested for ARS antibodies even when an ASSD is not clearly suspected. References: [1]Mirrakhimov AE. Curr Med Chem 2015;22:1963–75 [2]Cavagna L. J Clin Med 2019;8:E2013 [3]Sebastiani M. J Rheum 2019:46:279-84 [4]van den Hoogen F. Ann Rheum Dis 2013;72:1747-55 Disclosure of Interests: Giovanni Zanframundo: None declared, Gianluca Sambataro: None declared, Veronica Codullo: None declared, Alessandro Biglia: None declared, Emanuele Bozzalla Cassione: None declared, Elena Bravi: None declared, Florenzo Iannone Consultant of: Speaker and consulting fees from AbbVie, Eli Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, MSD, Speakers bureau: Speaker and consulting fees from AbbVie, Eli Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, MSD, Marco Fornaro: None declared, Konstantinos Triantafyllias: None declared, Alberto Pesci: None declared, Paola Tomietto: None declared, Øyvind Molberg: None declared, Salvatore Scarpato: None declared, Reinhard Voll: None declared, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Bristol-Myers Squibb, Speakers bureau: Acetelion, Lilly, Boehringer Ingelheim, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD, Carlomaurizio Montecucco: None declared, Lorenzo Cavagna: None declared